Supporting diagnosis and management of HIV/AIDS patients through point-of-care technology development. (September 2019) - McFall, Sally M.; Maiga, Mamoudou; Glucksberg, Matthew R.; Achenbach, Chad J.; Palamountain, Kara L.; Murphy, Robert L.
Abstract: The HIV pandemic disproportionately impacts sub-Saharan Africa where, in 2017, 71% of people living with HIV resided and 65% of new infections and 75% of deaths were reported. Prevention, screening, and treatment strategies have led to progress in addressing this disease. HIV diagnostics have been crucial for prevention and treatment, but more progress is required to reduce HIV infection. The C enter for Innovation in Point-of-Care T echnologies for H IV/A IDS at N orthwestern University (C-THAN) is a vital partner in the National Institute of Biomedical Imaging and Bioengineering Point-of-Care Technologies Research Network. C-THAN's mission is to develop and commercialize a pipeline of point-of-care technologies critical for improved prevention and management of HIV in low- and middle-income countries with specific emphasis on sub-Saharan Africa. Graphical abstract: Image 1 Highlights: UNAIDS 90-90-90 treatment target to be reached by 2020 will help end AIDS epidemic. Point-of-care technologies designed for HIV care cascade will help meet this target. C-THAN supports development and facilitates commercialization of POC technology. C-THAN focuses on HIV high-priority research topics within sub-Saharan Africa.